Guardianship, Its Importance and Developments: A Comparative Study Between Shariah Law and the Positive Law - Abdul Azeez Maruf Olayemi; Anthoney Gbadebo Olagunju (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Guardianship ‘Tutelae’ as a legal concept is as old as mankind. In antiquity, the communal and societal guardian is referred to as a messenger of God, prophet, priest and etc. He or she is believed to be a divine guardian that is appointed by God to lead each community or society, custodis mortalis. However, guardianship as an institution is not restricted to the communal and societal systems alone; it is also important to the family system and to the individual person when he or she is a minor or incapacitated. The institution is important to ensure that the interest of the present and future generations and the care of the people as o whole are preserved. However, the institution has positively undergone various developments in the present. Its importance and its transformations are discussed in this paper from the perspective of Shariah and Positive Laws.